Political Literacy: Why Do We Have to Come to The Voting Booth on Wednesday, 14ͭ ͪ February 2024 - Achmad Jamil; Rizki Briandana; Ari Sulistyanto (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Democracy is an indicator of the implementation of the highest legitimate state power by the people (popular sovereignty), which is manifested by their involvement in the democratic party (election). The higher the level of political participation, the more likely it is that the people will follow, understand, and involve themselves in state activities. On the other hand, a low level of political participation generally indicates that the people have little appreciation or interest in state issues or activities. New voters are citizens who are exercising their right to vote for the first time in general election activities. They can come from Indonesian citizens (WNI) who are 17 years old or not yet 17 years old but have already been married. Young voters in the general election are a new generation of voters who have different traits and characteristics, backgrounds, experiences, and challenges from voters in the previous generation. Most of them are students, have good economic status, and generally live in urban areas or surrounding areas. This research focuses on Indonesian migrant workers in Penang, Malaysia, regarding the upcoming 2024 elections. The purpose of this paper is to determine the forms of political participation of novice voters in elections, the factors supporting the political participation of novice voters in elections, and the factors inhibiting the political participation of novice voters in elections.